Spillovers between food and energy prices and structural breaks - Alanoud Al-Maadid; Guglielmo Maria Caporale; Fabio Spagnolo; Nicola Spagnolo (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
This paper estimates a bivariate VAR-GARCH(1,1) model to examine linkages between food and energy prices. The adopted framework is suitable to analyse both mean and volatility spillovers, and also allows for possible parameter shifts resulting from four recent events, namely: 1) the 2006 food crisis, 2) the Brent oil bubble, 3) the introduction of the Renewable Fuel Standard (RFS) policy, and 4) the 2008 global financial crisis. The empirical findings suggest that there are significant linkages between food and both oil and ethanol prices. Further, the four events considered had mixed effects, the 2006 food crisis and 2008 financial crisis leading to the most significant shifts in the (volatility) spillovers between the price series considered.
Keywords: C32; F36; G15; 330; Energy and food prices; VAR-GARCH BEKK model; Mean and volatility spillovers